Time saving method for protoplast isolation, transformation and transient gene expression assay in barley - Jenes, Barnabás; Puolimatka, Matti; Bittencourt, Pedro; Pulli, Seppo (Agricultural Research Centre of Finland, 1994)
Tutkimuksessa kehitettiin menetelmä, jossa protoplasteja eristetään suoraan ohran jyvien alkion ja sirkkakilven solukosta ilman edeltävää solukkoviljelyvaihetta. Jyvät pintasteriloitiin ja niitä liuotettiin steriloidussa vedessä vuorokausi. Tämän jälkeen alkion ja sirkkakilven solukot eristettiin jyvistä ja pilkottiin pieniksi paloiksi. Protoplastien eristämiseksi kokeiltiin aluksi kolmea erilaista entsyymiIiuosta, joista paras valittiin PEG (polyetyleeniglykoli) menetelmällä tehtyihin geeninsiirtokokeisiin. Siirtokokeissa käytetty rengasmainen plasmidi-DNA pAct1-F sisälsi riisin Act1-säätelyjakson, Gus-geenin (koodaa ß-glukuronidaasi-entsyymiä) ja Nos-lopetusjakson. PEG-käsittelyn jälkeen protoplasteja kasvatettiin KPR-kasvatusalustalla. Transienttinen (väliaikainen) Gus-geenin ilmentyminen määritettiin vuorokauden kuluttua käsittelemällä transformoituja protoplasteja X-gluc-entsyymisubstraatilla. Enimmillään noin kuudessa prosentissa transformoiduista protoplasteista havaittiin Gus-geenin ilmentymistä. Tulosten mukaan tämä nopea protoplastien eristystekniikka soveltuu erityisesti väliaikaisen geeni-ilmentymisen tutkimukseen, sillä ajansäästö protoplastien normaaliin suspensioviljelmään verrattuna on huomattava.

This study was conducted to establish a rapid method for barley (Hordeum vulgare L.) protoplast isolation to provide an easy-to-use procedure for the transformation and primary investigation of new gene constructs by transient gene expression assays. Protoplasts were successfully isolated from the chopped embryo and scutellum parts of mature barley seeds by digesting three hours with an enzyme mixture. Isolated protoplasts were washed in W5 washing solution, sieved through plastic meshes and then cleaned on sucrose gradient. The suitability of these directly from embryo-scutellum complexes derived protoplasts for transient gene expression studies was determined by transforming the protoplasts using the PEG (polyethylene glycol) method. Plasmid pAct1-F containing the rice Act1 promoter linked with the gus coding sequences and the nos polyadenylation signal was used in the transformation. After the PEG treatment protoplasts were cultured on KPR culture medium and the transient gus expression was assayed 24-36 hours after transformation. Up to 6% of the transformed protoplasts showed gus expression after treating the protoplasts with X-gluc. The results of this study show that the protoplasts isolated directly from dissected mature barley scutellum-embryo complexes could be used to investigate transient gene expressions in barley. This procedure requires negligible time prior the transformation experiment and so can be done in a very short time compared to the protoplast system based on a suspension culture.
Keywords: barley; ohra; Hordeum vulgare L.; plasmid; gene transfer; ß-glucuronidase